HPTLC, Physicochemical and Phytochemical Analysis of Kodo Millet (Paspalum scrobiculatum L.) Seeds with Special Reference to its Ethnopharmacological Review - Sinimol Thekkekkoottumughath Peethambaran; Sree Deepthi GN; Soumya MC; Sreenidhi Varma; Natarajan M (Pharmacognosy Research, 2024)
Background: Kodo millet, botanically (Paspalum scrobiculatum L.) is one among the minor millets cultivated mostly in Asian and African continents. Dr. M.S Swaminathan, father of Indian green revolution called all millets as orphan’s food. Moreover, most of these millets including Kodo millets have been in use since antiquity by the indigenous communities across the globe for medicinal purpose also. Ayurvedic science also indicates Kodo millet in the management of conditions like diarrhoeal disorders, wound, poison, bleeding disorders, Obesity, Ascitis. In the scenario of escalating significance of millets in light of the United Nations General Assembly's declaration of 2023 as "The International Year of Millets," a scientific analysis of Kodo millet is urgently needed in order to standardize and ensure its quality. Objectives: For the purpose of standardizing Kodo Millet seeds, HPTLC, physico-chemical and phytochemical analyses were carried out. Review of literature of its ethnopharmacological uses was also done, because its documentation is essential for creating awareness among the public and scientific community. Materials and Methods: HPTLC and physico-chemical analysis of Kodo millet seed were conducted. Alcoholic extraction (reflux) of seed powder was done for phytochemical analysis. The best fingerprint for HPTLC analysis was obtained using Toluene: Ethyl acetate: Methanol: Formic acid as the mobile phase (5:7:3:0.1). Review of literature of its ethnopharmacology was conducted by searching indexed journals and books. Results and Conclusion: Physicochemical analysis revealed identity and purity of Kodo millet grains. Proteins, glycosides, tannins and flavonoids were found to be the phytochemicals present in it. The peaks in the HPTLC fingerprint profile correlate to its different phytoconstituents and can be utilized to standardize the drug. Ethnopharmacological review revealed its use in many conditions like Diabetes mellitus, wound healing, bowel cleansing and inflammation. Moreover, it is even used in treating veterinary diseases like Ranikhet disease in poultry and Tympanic disease of cattle.
Keywords: Ethnopharmacology; HPTLC; Kodo Millet; Physicochemical; Phytochemical; Standardization